Circadian profile and chrono-structure of blood pressure in patients with arterial hypertension: desynchronosis as a risk factor in Far North shift workers - L. I. Gapon; N. P. Shurkevich; A. S. Vetoshkin; D. G. Gubin; N. B. Belozerova (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To study circadian profile (CP) and chrono-structure of blood pressure (BP) in patients with arterial hypertension (AH) and to assess the role of desynchronosis as an AH risk factor among Far North shift workers.Material and methods. CP and chrono-structure of BP were analysed in 393 men, aged 20-59 years. The main group (MG) included 177 AH patients – Far North shift workers. The comparison group (ComG) included 158 AH patients - Tyumen City residents. The control group (ConG) included 43 healthy Far North workers and 15 Tyumen City residents.Results. In Far North patients with AH, BP CP was characterised by desynchronosis and hypersympathicotonia, manifested in “flattened” BP CP curve, increased night-time hemodynamic load, elevated mean 24-hour diastolic BP (DBP) and reduced mean 24-hour systolic BP (SBP), phase discordance between BP CP and heart rate (HR), increased circadian heart rate variability, increased mean 24-hour HR, and significant differences between office and 24-hour levels of SBP and DBP. In the ComG and ConG, disturbed chrono-structure of BP and progressing endogenous and exogenous desynchronosis.Conclusion. Desynchronosis, as a manifestation of disturbed neuro-humoral regulation, could play an important role in AH development among patients adapting to extreme conditions of the Far North.